Conduct and reporting of formula milk trials: systematic review. (13th October 2021) - Helfer, Bartosz; Leonardi-Bee, Jo; Mundell, Alexandra; Parr, Callum; Ierodiakonou, Despo; Garcia-Larsen, Vanessa; Kroeger, Cynthia M; Dai, Zhaoli; Man, Amy; Jobson, Jessica; Dewji, Fatemah; Kunc, Michelle; et al.
Abstract: Objective: To systematically review the conduct and reporting of formula trials. Design: Systematic review. Data sources: Medline, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched from 1 January 2006 to 31 December 2020. Review methods: Intervention trials comparing at least two formula products in children less than three years of age were included, but not trials of human breast milk or fortifiers of breast milk. Data were extracted in duplicate and primary outcome data were synthesised for meta-analysis with a random effects model weighted by the inverse variance method. Risk of bias was evaluated with Cochrane risk of bias version 2.0, and risk of undermining breastfeeding was evaluated according to published consensus guidance. Primary outcomes of the trials included in the systematic review were identified from clinical trial registries, protocols, or trial publications. Results: 22 201 titles were screened and 307 trials were identified that were published between 2006 and 2020, of which 73 (24%) trials in 13 197 children were prospectively registered. Another 111 unpublished but registered trials in 17 411 children were identified. Detailed analysis was undertaken for 125 trials (23 757 children) published since 2015. Seventeen (14%) of these recently published trials were conducted independently of formula companies, 26 (21%) were prospectively registered with a clear aim and primary outcome, and authors or sponsors shared prospective protocols for 11 (9%) trials. Risk of bias was low in five (4%) and high in 100 (80%) recently published trials, mainly because of inappropriate exclusions from analysis and selective reporting. For 68 recently published superiority trials, a pooled standardised mean difference of 0.51 (range −0.43 to 3.29) was calculated with an asymmetrical funnel plot (Egger's test P<0.001), which reduced to 0.19 after correction for asymmetry. Primary outcomes were reported by authors as favourable in 86 (69%) trials, and 115 (92%) abstract conclusions were favourable. One of 38 (3%) trials in partially breastfed infants reported adequate support for breastfeeding and 14 of 87 (16%) trials in non-breastfed infants confirmed the decision not to breastfeed was firmly established before enrolment in the trial. Conclusions: The results show that formula trials lack independence or transparency, and published outcomes are biased by selective reporting. Systematic review registration: PROSPERO 2018 CRD42018091928.